Microbial, Chemical, Antioxidant and GC-MS investigation of Bioactive Compounds in ‘Ogiri’ Produced from Raw and Fermented Citrullus lanatus Seeds - Babatuyi, C. Y.; Oguntimehin, M. O. (Journal of Science, Technology and Innovation Research, 2025)
The dominant population pressure in Nigeria has led to a rising need for wild underutilized plant seeds and aesthetically pleasing goods in the daily diet. apart from nutritional attributes. African condiment (‘ogiri’) is seasoning food condiment that also serve a low protein and calorie food intake for village dwellers who cannot afford protein. Freshly harvested purchased deshelled Citrullus lanatus seeds (50 kilograms) were sorted, washed, boiled for 2 h before fermentation to produce ‘ogiri’ for 14 days. The microbial isolation, chemical measurements were made throughout the fermentation process. were carried out during the fermentation. The microbial ecology (load and population), nutritional, bioactive compounds and antioxidant properties were determined. The microbial successions of Bacteria and Fungi (Aspergillus niger, Rhizopus sp., Saccharomyces sp. and Candida albicans) were found throughout the fermentation period. The pH increased from 6.1 to 8.2 and TTA decreased from 0.1% to 0.025%. The fermented sample had its mineral elements higher than the raw except on lead; likewise, the proximate and antioxidants had more proximate, and antioxidants compared to the raw sample. Bioactive compounds had the highest area and height at peak 12 with higher concentrations of the following compounds. Their formula C18H34O2, C15H30O, C18H36O, C16H30O2, C13H24O2 respectively. Therefore, the ‘ogiri’ produced from Citrullus lanatus seeds may be incorporated into the food system.